AUDIT APLIKASI DEVELOP INTERNAL DENGAN COBIT 4.1 (STUDI KASUS : PT CENTRAL MEGA KENCANA) - Kevin Christianto; Leonard Davinci; Titus Zefanya Ivgantius; Yosep Prasetyo Setiawan; Timothy Jason Andreas (Universitas Bunda Mulia, 2019)
Information technology is an important part for companies or institutions as a thing that can support the achievement of strategic plans to achieve the goals of vision, mission and corporate goals PT.Central Mega Kencana. By increasing the role of information technology, investment in information technology is getting bigger and more complex in its management. Therefore To organize, evaluate the required information technology governance by using standardized obeject approach. The governance of this information system audit is done using the AI (acquired and implemented) Cobit 4.1 framework and the final result of this analysis yields how far the level of maturity level governance maturity and recommendations for PT. Central Mega Kencana proposed.